2021
DOI: 10.2459/jcm.0000000000001253
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter aortic valve implantation in patients with unruptured aortic root pseudoaneurysm: an observational study

Abstract: Aims Unruptured aortic root pseudoaneurysm (UARP) is a rare complication of aortic valve endocarditis. Infectious spread to the valvular annulus or myocardium can cause septic complications that manifest as wall thickening, and spontaneous abscess drainage leads to pseudoaneurysm formation. We report the first patient series in which transcatheter aortic valve implantation (TAVI) using a single valve-resolved aortic valvulopathy associated with UARP was performed.Methods At our center, from December 2017 to Oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Some studies have reported on the adoption of techniques such as a placement of a stent graft and transcatheter aortic valve implantation and the use of occluder devices vascular plugs to exclude pseudoaneurysm (7,8). However, little information on whether endovascular therapy is suitable for progressive pseudoaneurysm patients is available (9).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported on the adoption of techniques such as a placement of a stent graft and transcatheter aortic valve implantation and the use of occluder devices vascular plugs to exclude pseudoaneurysm (7,8). However, little information on whether endovascular therapy is suitable for progressive pseudoaneurysm patients is available (9).…”
Section: Discussionmentioning
confidence: 99%
“…A preoperative multislice computed tomography scan (MSCT) is generally performed to assess the valve complex, define the access site, and avoid complications [ 6 , 7 ] ( Figure 1 ). So far, several alternative access routes for antegrade or retrograde TAVI procedures have been described, namely the transfemoral, transaortic, transapical, transcarotid and transaxillary access routes [ 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…A preoperative multislice computed tomography scan (MSCT) is generally performed to assess the valve complex, define the access site, and avoid complications [6,7] (Figure 1).…”
Section: Introductionmentioning
confidence: 99%